GAMBARAN KUALITAS HIDUP PENDERITA RINOSINUSITIS KRONIS BERDASARKAN SINO NASAL OUTCOME TEST 22 DI RUMAH SAKIT UMUM DELI SERDANG - PRISCILLYA FITRI CINTHYA INDRA; SITI MASLIANA SIREGAR (LP2MTBM MAKARIOZ, 2020)
Chronic rhinosinusitis significantly decreases the quality of life of patients due to symptoms that usually appear. For chronic diseases such as rhinosinusitis, the patient's quality of life is important in monitoring the severity of the disease. Studies show more than 75% of patients with chronic rhinosinusitis, have poor quality of life according to the severity of rhinosinusitis. Due to the high prevalence of chronic rhinosinusitis in Indonesia, as evidenced by data from the Department of Health of the Republic of Indonesia in 2003, where nasal and sinus disease was ranked 25th out of 50 patterns of major ranking diseases, researcher are interesting in seeing a representation of the quality of life for chronic rhinosinusitis patients. To determine the representation quality of life of patients with chronic rhinosinusitis in ear nose throat polyclinic of the general hospital deli serdang. This research use descriptive method with cross sectional design. The population of this study was all chronic rhinosinusitis patients at Deli Serdang General Hospital. The highest proportion of patients with chronic rhinosinusitis, in the age group of 16-25 years (45,5%), with the proportion of women (59.1%), chronic rhinosinusitis with poor quality of life as much as 44 people (100%). Chronic rhinosinusitis show poor health-related quality of life in patients.